Perubahan UU ITE: Upaya Perlindungan atau Pembatasan Hak Digital? Sebuah Analisis terhadap Reformulasi Norma Pidana Siber di Indonesia - Gilang Rizki Aji Putra (BULETIN ADALAH, 2021)
The second amendment to the Electronic Information and Transactions Law introduces key changes, including the affirmation of ultimum remedium and reduced criminal sanctions. This article critically examines whether these reforms genuinely strengthen digital rights protection or merely repackage restrictive norms. Using normative legal research with statutory, conceptual, and comparative approaches, the study finds that while the amendments improve safeguards, structural gaps remain, particularly the absence of ex ante filtering and vague definitions. Enforcement practices also show inconsistency. The reform is a partial, paradoxical step that still risks limiting fundamental digital rights. Keywords: ITE Law Amendment, Digital Rights, Ultimum Remedium, Freedom of Expression, Criminalization